Cover Feature: Coupling Glucose Dehydrogenation with CO2 Hydrogenation by Hydrogen Transfer in Aqueous Media at Room Temperature (ChemSusChem 13/2018). Issue 13 (2nd July 2018) - Ding, Guodong; Su, Ji; Zhang, Cheng; Tang, Kan; Yang, Lisha; Lin, Hongfei
Abstract : The Cover Feature shows a novel synergistic catalytic process for co‐producing formate, gluconate, and sorbitol that is developed by coupling the dehydrogenation of glucose with the hydrogenation of CO2 ‐derived salt in an aqueous ethanol solvent under ambient conditions. More information can be found in the Communication by Ding and Su et al. on page 2029 in Issue 13, 2018 (DOI: 10.1002/cssc.201800570 ).